2014
DOI: 10.1080/02640414.2013.877593
|View full text |Cite
|
Sign up to set email alerts
|

Landing ground reaction forces in figure skaters and non-skaters

Abstract: Researchers and clinicians have suggested that overuse injuries to the lower back and lower extremities of figure skaters may be associated with the repeated high impact forces sustained during jump landings. Our primary aim was to compare the vertical ground reaction forces (GRFs) in freestyle figure skaters (n = 26) and non-skaters (n = 18) for the same barefoot single leg landing on a force plate from a 20 cm platform. Compared with non-skaters, skaters exhibited a significantly greater normalised peak GRF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…Although half-pipe snowboarders were familiar with the landing tasks, they showed a significantly higher peak vGRF (by 20%) than the untrained participants, regardless of the 30 cm or 60 cm drop heights. Our result is consistent with that of other studies (Christoforidou et al, 2017; Saunders et al, 2014; Seegmiller & McCaw, 2003). Saunders et al (Saunders et al, 2014) compared the difference in peak vGRF when landing from a 20 cm platform between figure skaters and nonskaters, and found that figure skaters exhibited a significantly higher normalized peak vGRF (3.50 × bodyweight for skaters vs. 3.13 × bodyweight for non-skaters), with skaters showing an approximately 15% higher peak vGRF.…”
Section: Discussionsupporting
confidence: 94%
“…Although half-pipe snowboarders were familiar with the landing tasks, they showed a significantly higher peak vGRF (by 20%) than the untrained participants, regardless of the 30 cm or 60 cm drop heights. Our result is consistent with that of other studies (Christoforidou et al, 2017; Saunders et al, 2014; Seegmiller & McCaw, 2003). Saunders et al (Saunders et al, 2014) compared the difference in peak vGRF when landing from a 20 cm platform between figure skaters and nonskaters, and found that figure skaters exhibited a significantly higher normalized peak vGRF (3.50 × bodyweight for skaters vs. 3.13 × bodyweight for non-skaters), with skaters showing an approximately 15% higher peak vGRF.…”
Section: Discussionsupporting
confidence: 94%
“…Contemporary skates limit the ability of the human body to deal with impact forces during jump landings due to the stiffness and the high heel of the skates. Several studies are in agreement indicating that a reduced ability of the human body to deal with impact forces may be at least partially attributed to the restriction of ankle motion and the high heel (Bruening & Richards, 2006;Dubravcic-Simunjak et al, 2003;Haguenauer, Legreneur & Monteil, 2006;King, 2000;King, Arnold & Smith, 1994;Porter et al, 2007;Saunders, Hanson, Koutakis, Chaudhari, & Devor, 2014). Restriction of ankle motion in skates is largely caused by the stiffness of the skates, but the stiffness of footwear is also important in order to secure the ankle joint against excessive motion (B€ ohm & H€ osl, 2010;Campanelli et al, 2015;Cordova, Takahashi, Kress, Brucker, & Finch, 2010;Rowley & Richards, 2015), which is especially necessary during demanding jumps, spins, and steps on the ice.…”
Section: Introductionmentioning
confidence: 81%
“…In addition, dynamic balancing assessment may be more appropriated with a sport-related method (e.g. jump landing evaluation) [2,12,13,26,36] even if some authors claimed to evaluate dynamic balancing through static postural control or joint position sense reproduction tests [37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for the dynamic balancing test, timeto-stabilisation in the vertical (vTTS), anterior-posterior (APTTS) and medial-lateral (MLTTS) directions were calculated taking all the three components of the GRFs. For all directions, data from the initial fourteen seconds after landing were used to calculate means and SDs of each trial and TTS was defined as the time when cumulative average of the relevant component of the GRF signal remained within mean + 0.25 SD of the trial [13,36]. Maximum vertical landing force (Fmax) were evaluated for each trial using vertical GRF data while maximum jump height (JH) was taken from marker vertical displacement data.…”
Section: Data Processingmentioning
confidence: 99%